The molecular basis of phosphite and hypophosphite recognition by ABC-transporters. Issue 1 (December 2017) - Bisson, Claudine; Adams, Nathan; Stevenson, Ben; Brindley, Amanda; Polyviou, Despo; Bibby, Thomas; Baker, Patrick; Hunter, C. Neil; Hitchcock, Andrew
Abstract Inorganic phosphate is the major bioavailable form of the essential nutrient phosphorus. However, the concentration of phosphate in most natural habitats is low enough to limit microbial growth. Under phosphate-depleted conditions some bacteria utilise phosphite and hypophosphite as alternative sources of phosphorus, but the molecular basis of reduced phosphorus acquisition from the environment is not fully understood. Here, we present crystal structures and ligand binding affinities of periplasmic binding proteins from bacterial phosphite and hypophosphite ATP-binding cassette transporters. We reveal that phosphite and hypophosphite specificity results from a combination of steric selection and the presence of a P-H…π interaction between the ligand and a conserved aromatic residue in the ligand-binding pocket. The characterisation of high affinity and specific transporters has implications for the marine phosphorus redox cycle, and might aid the use of phosphite as an alternative phosphorus source in biotechnological, industrial and agricultural applications. Some bacteria can use inorganic phosphite and hypophosphite as sources of inorganic phosphorus. Here, the authors report crystal structures of the periplasmic proteins that bind these reduced phosphorus species and show that a P-H…π interaction between the ligand and binding site determines their specificity.